2016
DOI: 10.1074/jbc.m116.748814
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Production Mediated by Lipid Metabolism Suppresses the Physical Interaction of Peroxisomes and Oil Bodies during Germination of Arabidopsis thaliana

Abstract: Physical interaction between organelles is a flexible event and essential for cells to adapt rapidly to environmental stimuli. Germinating plants utilize oil bodies and peroxisomes to mobilize storage lipids for the generation of sucrose as the main energy source. Although membrane interaction between oil bodies and peroxisomes has been widely observed, its underlying molecular mechanism is largely unknown. Here we present genetic evidence for control of the physical interaction between oil bodies and peroxiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 59 publications
(81 reference statements)
1
54
0
Order By: Relevance
“…Fatty acids may be transported from oil bodies to glyoxysomes via small vesicles originating from the oil body, rather than free diffusion through the cytosol. In support of this hypothesis, PED3 is enriched significantly on the dendritic tubule membrane where the vesicles may dock (Cui et al, 2016). A recent study observed the retrograde flow of membranous structures from glyoxysomes to oil bodies in plant cells (Thazar-Poulot et al, 2015).…”
Section: Physical Interaction Between Oil Bodies and Glyoxysomes In Hsupporting
confidence: 48%
See 1 more Smart Citation
“…Fatty acids may be transported from oil bodies to glyoxysomes via small vesicles originating from the oil body, rather than free diffusion through the cytosol. In support of this hypothesis, PED3 is enriched significantly on the dendritic tubule membrane where the vesicles may dock (Cui et al, 2016). A recent study observed the retrograde flow of membranous structures from glyoxysomes to oil bodies in plant cells (Thazar-Poulot et al, 2015).…”
Section: Physical Interaction Between Oil Bodies and Glyoxysomes In Hsupporting
confidence: 48%
“…Cytological observations of the Arabidopsis specific triacylglycerol lipase (sdp1) mutant revealed that the close proximity of oil bodies and glyoxysomes is strictly regulated by the intracellular Suc concentration, which is an end product of triacylglycerol catabolism (Cui et al, 2016). Arabidopsis cells contain substantial oil body aggregates during early seedling growth.…”
Section: Physical Interaction Between Oil Bodies and Glyoxysomes In Hmentioning
confidence: 99%
“…Although peroxisomes and oil bodies interact in Arabidopsis (Hayashi et al ., ; Schumann et al ., ; Thazar‐Poulot et al ., ), the molecular details of the relationship are incompletely understood. Peroxisome–oil body clustering is heightened when Arabidopsis seedlings are grown without sucrose (Cui et al ., ). We observed peroxisomes nestled around persisting oil bodies in pex6‐1 , pex6‐3, pex6‐4 , and pex26‐1 even when supplemented with sucrose (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, these metabolic interactions may involve dynamic and reversible functional and morphological adaptations between peroxisomes and other organelles such as chloroplasts and oil bodies during physiological processes such as photorespiration [19], [51], [84] and seed germination [35] which enable metabolic exchanges between the organelles to be optimized [63]. So far, over 300 plant peroxisomal proteins have been identified [69], [93]; however, innovative approaches using proteomic and bioinformatic technologies, with the combination of highly purified peroxisomes from different plant tissues at different developmental stages, have brought to light new and unexpected components with hitherto unknown functions [3], [47], [60], [62], [71], [88], [99].…”
Section: Introductionmentioning
confidence: 99%